Pendidikan Agama Kristen di Era Digital Ada Tantangan dan Peluang Baru - Doni A (International Forum of Researchers and Lecturers, 2024)
The development of information and communication technology has changed the landscape of education as a whole, including in the context of Christian Religious Education (PAK). This article aims to review the challenges, negative impacts, new opportunities and use of technology in PAK in the digital era. In dealing with this problem, the research method used involves qualitative analysis with data synthesis from various related studies. The research results show that the integration of technology in PAK has the potential to improve learning content, increase student engagement, and create a more interactive learning experience. However, it is important to note that there are negative impacts of the digital era, such as the risk of dependence on technology, which also need to be considered in the context of religious learning. However, there are new opportunities offered by technological developments and how to use them at PAK. This includes the use of various methods and platforms that support interactive and creative learning, which can help increase students' understanding of Christianity in the digital era. Thus, the use of technology in PAK is not only about exploiting the advantages of technology to improve teaching, but also about understanding and overcoming the challenges and negative impacts that may arise. Only with a balanced approach between the use of technology and an understanding of its specific context, can Christian religious education in the digital era become more effective and relevant for the younger generation.